Polyclonal carbapenemase-producing Escherichia coli in Northern Italy: the emergence of NDM-7 - Mattioni Marchetti, Vittoria; Corbella, Marta; Piazza, Aurora; Gaiarsa, Stefano; Mileto, Irene; Merla, Cristina; Kuka, Angela; AbuAlshaar, Aseel; Cambieri, Patrizia; Migliavacca, Roberta; Baldanti, Fausto (Frontiers in Cellular and Infection Microbiology, 2025)
The spread of extended-spectrum beta-lactamase (ESBL)- and carbapenemase-producing Escherichia coli clones in humans, animals, and the environment is of great concern worldwide. In this study, we characterized four carbapenemase-producing E. coli (CP-Ec) isolated from human samples. Two isolates of ST401, rarely associated with carbapenemase and/or ESBL resistance genes, harbored blaKPC-3 and blaVIM-1 genes, respectively, and were genetically distant from each other. One CP-Ec isolate belonging to ST355, typically found in poultry and environmental sources and not associated with carbapenemases, was blaKPC-3 positive and showed a wide range of virulence genes. The last CP-Ec strain belonged to ST3564, previously described in livestock with a large virulome but no carbapenemase. The CP-Ec ST3564 isolate co-harbored blaVIM-1 and blaNDM-7 genes, which, to our knowledge, have not been previously reported in Italy. These results emphasize the crucial role of a genomic-based surveillance program to intercept the emergence of critical E. coli clones.